Personality trait level and change predict future financial well-being: A longitudinal study in Australia - Joshanloo, Mohsen (My University, 2022)
This study examined whether Big Five personality traits and their longitudinal trajectories can predict future levels of subjective financial well-being. Data were obtained from the Household, Income, and Labour Dynamics in Australia (HILDA) survey (N = approximately 11,300). Personality traits were measured four times between 2005 and 2017, while subjective financial well-being was measured in 2020 and served as a distal outcome. Results of latent growth curve analysis showed that initial levels of emotional stability and conscientiousness and their rates of change predicted future levels of subjective financial well-being. Individuals with higher initial levels and larger increases in emotional stability and conscientiousness were more likely to have higher future levels of financial well-being.
Personality and Individual Differences
Keywords: Culture and language; Income, wealth and finances